Determination of Target Sequence Bound by PapX, Repressor of Bacterial Motility, in flhD Promoter Using Systematic Evolution of Ligands by Exponential Enrichment (SELEX) and High Throughput Sequencing - Reiss, Daniel J. (American Society for Biochemistry and Molecular Biology, 2011)
Most uncomplicated urinary tract infections (UTIs) are caused by uropathogenic Escherichia coli (UPEC). Both motility and adherence are integral to UTI pathogenesis, yet they represent opposing forces. Therefore, it is logical to reciprocally regulate these functions. In UPEC strain CFT073, PapX, a non-structural protein encoded by one of the two pap operons encoding P fimbria adherence factor, represses flagella-mediated motility and is a putative member of the winged helix transcription factor family. The mechanism of this repression, however, is not understood. papX is found preferentially in more virulent UPEC isolates, being significantly more prevalent in pyelonephritis strains (53% of isolates) than in asymptomatic bacteriuria (32%) or fecal/commensal (12.5%) strains. To examine PapX structure-function, we generated papX linker insertion and site-directed mutants, which identified two key residues for PapX function (Lys(54) and Arg(127)) within domains predicted by modeling with I-TASSER software to be important for dimerization and DNA binding, respectively. To determine the PapX binding site in the CFT073 genome, systematic evolution of ligands by exponential enrichment (SELEX) in conjunction with high throughput sequencing was utilized for the first time to determine a novel binding site for a bacterial transcription factor. This method identified a 29-bp binding site within the flhDC promoter (TTACGGTGAGTTATTTTAACTGTGCGCAA), centered 410 bp upstream of the flhD translational start site. Gel shift experiments demonstrated that PapX binds directly to this site to repress transcription of flagellar genes.